The Problem of Proving Genocidal Intent and Its Impact on Accountability in International Criminal Law - Hawa Salehi (Fakultas Hukum Universitas Islam Indonesia, 2026)
This paper discusses the issue of establishing the genocidal intent (dolus specialis) and its effect on criminal responsibility within international criminal law. It seeks to determine the suitability of existing judicial criteria in determining such intent. The study examines the jurisprudence of ICTR, ICTY, and ICC by using the normative legal research approach, which analyzes the Genocide Convention, the Rome Statute, and convention jurisprudence. The results show that the international courts use indirect and contextual evidence primarily to establish the presence of genocidal intent, so the evidentiary threshold is high, and this has restricted the conviction of genocide offenders.